NKG2A Complexed with CD94 Defines a Novel Inhibitory Natural Killer Cell Receptor - Brooks, Andrew G. (The Rockefeller University Press, 1997)
CD94 is a C-type lectin expressed by natural killer (NK) cells and a subset of T cells. Blocking studies using anti-CD94 mAbs have suggested that it is a receptor for human leukocyte antigen class I molecules. CD94 has recently been shown to be a 26-kD protein covalently associated with an unidentified 43-kD protein(s). This report shows that NKG2A, a 43-kD protein, is covalently associated with CD94 on the surface of NK cells. Cell surface expression of NKG2A is dependent on the association with CD94 as glycosylation patterns characteristic of mature proteins are found only in NKG2A that is associated with CD94. Analysis of NK cell clones showed that NKG2A was expressed in all NK cell clones whose CD16-dependent killing was inhibited by cross-linking CD94. The induction of an inhibitory signal is consistent with the presence of two immunoreceptor tyrosine-based inhibitory motifs (V/LXYXXL) on the cytoplasmic domain of NKG2A. Similar motifs are found on Ly49 and killer cell inhibitory receptors, which also transmit negative signals to NK cells.